The Classification of Polish Mutual Balanced Funds Based on the Management Style - Quantile Regression Approach - Orwat-Acedańska, Agnieszka; Trzpiot, Grażyna (Klasyfikacja polskich funduszy inwestycyjnych zrównoważonych ze względu na styl zarządzania - podejście regresji kwantylowej, 2011)
Style Analysis allows to assess impact of factors representing investments in asset classes on funds' rate of returns. When distribution of return rates is asymmetric, the application of classical Sharpe Style Analysis may lead to incorrect inference about model coefficients. Quantile Style Analysis investigates dependencies between fund returns and the risk factors for the quantile of the distribution. The paper's aim is to investigate the impact of the investments in the stocks and bonds on the balanced mutual funds returns by Quantile Style Analysis and to assess the usefulness of the quantile approach to the style analysis of the funds. We compare both the style shares for different quantiles for given fund and the funds classifications according to the style shares obtained for quantile and classic approach
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 9-23
Keywords: regresja kwantylowa; fundusze inwestycyjne; styl zarządzania; quantile regression; investment funds; management style